1994
DOI: 10.1590/s0101-81751994000200003
|View full text |Cite
|
Sign up to set email alerts
|

Seis novas larvas do gênero Micrathyria Kirby e notas sobre a distribuição no Brasil (Odonata, Libellulidae)

Abstract: SI)(NEW LARVAE OF GENUS MICRA71IYRIA KIRBY ANO NOTES ON DISTRIBl'I'ION lN BRAZIL (OI1ONATA. LIHELLl IUIlAE). Six new Micralhyria Kirby, 1889 larvae from Brazil ar~ d~scrih~d and compa r~d to thosc d~scrihcd by SANTOS (1968, 1972. 1978) and NEEDHAM (1943). The distribution ofthe speeies is studied based on mat~rial d~posited in colection 01' MlIs~lI Nacional. Universidad~ Federal do Rio de Jan~iro (MN-UFRJ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Essas espécies pertencem a gêneros relacionados a ambientes lênticos como brejos e poças, associados a macrófitas e detritos (e.g. CALVERT 1956;SANTOS 1968SANTOS , 1970bCARVALHO1991;ASSIS & COSTA 1994;NESSIMIAN 1995a, b;DE MARCO & LATINI 1998). O fato de essas espécies terem sido encontradas no Rio Ubatiba demonstra que o substrato vegetação de remanso pode ter, em alguns meses, características semelhantes à de ambientes lênticos, permitindo o estabelecimento dessas espécies.…”
Section: Resultsunclassified
“…Essas espécies pertencem a gêneros relacionados a ambientes lênticos como brejos e poças, associados a macrófitas e detritos (e.g. CALVERT 1956;SANTOS 1968SANTOS , 1970bCARVALHO1991;ASSIS & COSTA 1994;NESSIMIAN 1995a, b;DE MARCO & LATINI 1998). O fato de essas espécies terem sido encontradas no Rio Ubatiba demonstra que o substrato vegetação de remanso pode ter, em alguns meses, características semelhantes à de ambientes lênticos, permitindo o estabelecimento dessas espécies.…”
Section: Resultsunclassified
“…The remaining material was cleaned in a 0.25 mm mesh sieve for invertebrate sorting. The biological material was fixed in 4% formaline, then sorted and identified according to relevant specialized literature (Reid, 1982;MatsumuraTundisi, 1986;Epler, 1992;Assis & Costa, 1994;Lopretto & Tell, 1995;Merrit & Cummins, 1996;Elmoor-Loureiro, 1997) and the density (ind.g.DW -1 ) calculated. The trophic level of the functional groups of invertebrates living in Eichhornia azurea was determined according to information in Pennak (1991) and Merrit & Cummins (1996).…”
Section: The Experimentsmentioning
confidence: 99%
“…The exuviae of M. aequalis have 9–10 setae on the labial palps, while those of M. ocellata have 12 premental setae and 12–14 setae on the labial palps and those of M. mengeri have 10 premental setae and 10 setae on the labial palps. Micrathyria mengeri has only two brown bands on the femur and tibia ( Assis & Costa 1994) . Novelo-Gutiérrez & Arce-Pérez (2021) described the larva of M. paulsoni , comparing it with the similar M. didyma and M. hypodidyma , and found that M. paulsoni has only 10 setae on the labial palps, vs 12 in M. didyma.…”
Section: Discussionmentioning
confidence: 99%